The handbook of fixed income securities - Fabozzi, Frank J (New York : McGraw-Hill Education, 2021)
"The definitive guide to fixed income securities-updated and revised with everything you need to succeed in today's market For nearly 40 years, The Handbook of Fixed Income Securities has been providing comprehensive, current, reliable information on everything investors like you need to stay on top of the market and ahead of the curve. The fixed income market has changed dramatically in the past decade. This updated classic brings you fully up to date for a much-changed world of finance, where central banks play a bigger role, interest is low (and sometimes even in negative territory), regulations are more complex, and new types of securities have been created. Brand-new chapters cover: Relative value trades Muni analytics Financial data science Building and maintaining a bond portfolio Factor investing Relative value trades Smart beta fixed income Infrastructure and green bonds Sovereign bond markets One of the world's leading experts on fixed income securities, Frank Fabozzi has gathered a peerless team of global experts who provide the newest and best techniques for winning in today's markets. Fixed Income Securities, Ninth Edition is a matchless, one-stop resource for all your professional needs"--
Includes bibliographical references and index.
Keywords: Bonds -- Handbooks, manuals, etc; Preferred stocks -- Handbooks, manuals, etc; Money market funds -- Handbooks, manuals, etc; Mutual funds -- Handbooks, manuals, etc; Fixed-income securities -- Handbooks, manuals, etc